Managing Social Media Contents as the Digital Journalism Practice in the Indonesian EFL Students Context - Mulatsih, Maria Eka; Wulandari, Mega; Ardi, Priyatno (LPPM Universitas Mercu Buana Yogyakarta, 2022)
Technological developments in this digital era have changed the way people get information, both formal news and entertainment. This affects the nature of journalism which was previously asynchronous into real-time. The rapid flow of information demands English department students to be proficient in processing information and produces news content especially through digital platforms such as social media. This study seeks to answer a question: How did students manage social media as the practice of digital journalism? Experiential qualitative research method was applied to gather the data and its results were presented qualitatively. It was found that there were five steps in managing social media as the practice of digital journalism, namely: (1) deciding kind of timeless or real time news, (2) determining the news columns, (3) presenting the institution identity through color theme and layout, (4) distributing tasks and (5) implementing the news production